Predictive value of geriatric nutritional risk index for pulmonary infections in hospitalized elderly patients with type 2 diabetes mellitus - LIAN Mingzhu; ZHANG Changxiao; SHENG Kai; GUO Meng; FANG Shuyu (Shanghai Jiaotong Daxue xuebao. Yixue ban)
Objective·To investigate the predictive value of the geriatric nutritional risk index (GNRI) for the occurrence of lung infection in hospitalized elderly patients with type 2 diabetes mellitus (T2DM).Methods·Elderly T2DM patients who were admitted to the Geriatric Department of Shanghai Tongren Hospital between June 2022 and June 2024 were retrospectively and consecutively enrolled. They were divided into infected and non-infected groups according to whether lung infection occurred during hospitalization. Baseline data (gender, age, height, weight, duration of diabetes, comorbidities, etc.) were collected and GNRI was calculated. A multivariate Logistic regression model was used to screen the independent risk factors for pulmonary infections,and the predictive value of GNRI for pulmonary infections in T2DM patients was analysed using receiver operating characteristic (ROC) curves.Results·A total of 264 elderly T2DM patients were enrolled, among whom 154 developed pulmonary infections. Significant differences were observed between the infected and non-infected groups in GNRI, albumin, leukocyte count, neutrophil ratio, lymphocyte ratio, glycated hemoglobin, fasting glucose, interleukin-6, C-reactive protein, and procalcitonin levels (P<0.05). Multivariate Logistic regression analysis showed that a lower GNRI was an independent risk factor for lung infection (OR=0.798, 95%CI 0.712‒0.894; P<0.001). Correlation analysis showed that GNRI was negatively correlated with C-reactive protein and calcitoninogen. ROC curve analysis showed that GNRI predicted pulmonary infection with an area under the curve of 0.828, a sensitivity of 77.9%, and a specificity of 76.6%.Conclusion·A lower GNRI is an independent risk factor for pulmonary infections in elderly T2DM patients, and also has a good predictive value for the occurrence of pulmonary infections.